Ultrasound-enhanced adsorption of anionic and cationic dyes onto Azolla microphylla–derived green hydrochar as a low-cost and sustainable adsorbent - Wahyu Setiawan; Siska Nuri Fadilah; Subriyer Nasir; Muhammad Said; Muhammad Fauzul Imron; Tri Pebrianti; Putri Nurhafizah; Fakhili Gulo (Biomass and Bioenergy, 2027)

Heavy metal(loid)s contamination status in the Indus River Basin: A systematic review with Spatial Analysis and Risk Assessment - Tofeeq Ahmad; Said Muhammad; Alaa Ahmed (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Nutrient Enrichment Patterns and Spatial Heterogeneity in Enne Dam Lake (Sakarya River Watershed, Türkiye): Insights for Watershed Management Strategies - Cem Tokatlı; Said Muhammad; Alper Uğurluoğlu; Ahmet Bahtiyar Arvas; Rahmatullah Hakımı; İlker Manav; İsmail Yoşumaz; Caner Dilber (Water, Air, & Soil Pollution, 2026)

Contamination levels, eco-health risks, and source identification of some potentially toxic elements in roadside dust along the Indus Highway (N-55), Pakistan using compositional data analysis - Amanullah; Wajid Ali; Saad Khan; Said Muhammad; Abdur Raziq; Muhamamd Nafees; Imran Ud Din (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Germination-driven biochemical remodeling of cereals and pseudocereals: Impacts on nutrient bioaccessibility, phytochemical enrichment, and functional food potential - Djilali Benabdelmoumene; Muhammad Waqar; Abderahman Shawky; Omnia Darwish Askar; Wasim S.M. Qadi; Said Dahmouni; Mariam Gamaleldin; Faidruz Azura Jam; Ahmed Mediani; Hamizah Shahirah Hamezah; Habsah Aziz; Sajad Ali; et al. (Food Chemistry, 2026)

Numerical Analysis of Altitude Effects on Single-Cylinder Two-Stroke UAV Engine Performance - Muhammad Nouman Rashid; Faiq Said; Syed Ghafoor Shah; Muhammad Bilal; Hamza Sultan; Muhammad Qail (Next Research, 2026)

Pollution signatures of potentially toxic elements in rivers discharging to the Marmara Sea (Türkiye): ecotoxicological insights and Monte Carlo-based health risk assessment - Cem Tokatlı; Said Muhammad; Bayram Yüksel; Mehmet Metin Yazman; Fikret Ustaoğlu (Environmental Geochemistry and Health, 2026)

Geochemical Characterization of Saidgai and Katora Lakes for Irrigation, Drinking, and Health Risk Indices, Hindu Kush Region - Said Muhammad; Tufail Ahmad; Wajid Ali; Adnan Ali Khan; Cem Tokatli; Ashfaq Ahmad; Zafar Iqbal (Water, Air, & Soil Pollution, 2026)

Infectious clone–based dissection of delayed pathogenicity and evolutionary dynamics of Papaya leaf curl Guangdong virus (PaLCuGdV) - Renshu Huang; Muhammad Arif; Amna Saeed; Cheng Song; Omer Beyhan; Muhammed Said Yolcu; Islem Abid (European Journal of Plant Pathology, 2026)
Papaya leaf curl Guangdong virus (PaLCuGdV) is an economically significant begomovirus, although its pathogenicity and evolutionary dynamics are poorly understood. This study involved the construction of a full infectious clone of PaLCuGdV, which was agroinoculated into Nicotiana benthamiana ( N. benthamiana ) to assess the infectivity and symptomatology. The infectious clone elicited typical begomoviral symptoms just at 28 days post-inoculation, signifying delayed pathogenicity. Infection efficiency varied with strain, with successful transmission achieved using Agrobacterium GV301, but not with EHA105 alone. Southern blot analysis confirmed active viral DNA replication solely in diseased plants. Comparative sequencing and recombination analysis identified numerous recombination events among worldwide PaLCuGdV isolates, with the newly defined strain serving as a primary recombinant progenitor. These findings indicate that PaLCuGdV displays delayed symptom expression, strain-specific infectivity, and evolutionary diversity driven by recombination, underscoring the value of infectious clone systems for functional and evolutionary studies of begomoviruses.

Rock–phosphate–enriched hydrochars derived from organic wastes: a sustainable amendment for multi-metal contaminated soil - Altaf Hussain Lahori; Monika Mierzwa-Hersztek; Nguyen Thi Lam; Sergij Vambol; Muhammad Iftikhar Hussain; Said Ali Akbar (Waste Management, 2026)

Impacts of climate change and local stressors on the coral community structure off the eastern coast of Pakistan - Amjad Ali; Azka Rafiq Malik; Naveed Ahmad; Gulab Said; Zulfiqar Ali Mirani; Seema Shafique; Habibul Hassan; Ateeque Rahman Khooharo; Faiz Muhammad (Regional Studies in Marine Science, 2026)

Seasonal variation of potentially toxic elements in lacustrine habitats in the Thrace region, Türkiye: ecological and human health implications - Cem Tokatlı; Said Muhammad (Environmental Geochemistry and Health, 2026)

Sources and ecotoxicological risk indices of OCP and PCBs residues in Shalateen sediments, Red Sea, Egypt - Tarek O. Said; Mohamed A. Hassaan; Safaa Ragab; Muhammad Arshad; Amany El Sikaily; Ahmed El Nemr (Marine Pollution Bulletin, 2026)

Reverse flotation of apatite from iron ore in a REFLUXTM flotation cell - Vaishakh Tholan; Sascha Heitkam; Muhammad Ziauddin; B. Ben Said; Natska Ericson; Martin Rudolph; Kerstin Eckert (Minerals Engineering, 2026)

Application of integrated coagulation-flocculation and biofilter for the treatment of food-processing industrial wastewater: Performances, microbial community, and cost analysis - Setiyono; Heru Susanto; Sudarno; Muhammad Abdul Kholiq; Arifudin; Fajar Eko Priyanto; Ahmad Shoiful; Sandia Primeia; Hana Salsabila; Nur Muhamad Fuad; Yosep Widi Nugraha; Veny Luvita; et al. (Journal of Water Process Engineering, 2026)

Insecticidal activity against mosquito larvae, leishmanicidal activity, and cytotoxicity against human cells of a synthesized thiourea compound and a column chromatography fraction (AF5) from the n-hexane soluble fraction of Artemisia scoparia - Mirza Gul; Muhammad Zahid; Hazrat Ali; Muhammad Said; Sajjad Ahmad (Journal of Asia-Pacific Entomology, 2026)

Spatial variation in water quality, their ecotoxicological risks, and source apportionment in the Marmara Sea Watershed, Türkiye - Cem Tokatlı; Said Muhammad; Fikret Ustaoğlu; Bayram Yüksel (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Radon concentration, its deterministic and probabilistic health risks through groundwater consumption, and spatial distribution - Said Muhammad; Fawad Hussain; Saeeda Yousaf; Zafar Iqbal; Umar Farooq; Ashfaq Ahmad (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Water Quality deterministic and Probabilistic Health Risks Assessment using Monte Carlo Simulation: Case Study from a Semi-Arid Region - Said Muhammad; Zeeshan Raza; Wajid Ali; Ashfaq Ahmad; Cem Tokatli; Imran Ud Din (Water, Air, & Soil Pollution, 2026)

Tackling marine pollution in the blue economy: Synergies between wastewater treatment technologies and governmental policies - Setyo Budi Kurniawan; Ali Roziqin; Azmi Ahmad; Mahasin Maulana Ahmad; Benedicta Dian Alfanda; Dwi Sasmita Aji Pambudi; Nor Sakinah Mohd Said; Peer Mohamed Abdul; Muhammad Fauzul Imron (Marine Pollution Bulletin, 2026)

Multi-stage gold mineralization in the Açdif orogenic deposit (Zenaga inlier, central Anti-Atlas, Morocco): Constraints from LA-ICP-MS analysis of pyrites and structural controls - Mohammed El Azmi; Mohamed Aissa; Azizi Moussaid; Hafid Mezougane; Said Ilmen; Panagiotis Voudouris; Mohmed Aissa; Ilyasse Loudaoued; Ait Addi Mohamed; Muhammad Souiri; Ilya Prokopyev; El Haouiti Issmail; et al. (Journal of African Earth Sciences, 2026)

Spatial distribution, source characterization, and risk indices of heavy metals pollution in the sediments of the Hindu Kush Lacustrine ecosystem - Said Muhammad; Zeeshan Ahmad; Cem Tokatli; Adnan Khan; Zafar Iqbal; Ashfaq Ahmad (Environmental Geochemistry and Health, 2026)

Green Practices, knowledge processes and women’s business performance in Pakistan’s manufacturing sector - Said Muhammad; Yin Zhichao; Sajjad Alam; Naveed Khan (Environment, Development and Sustainability, 2025)

Biochar and plant growth-promoting rhizobacteria: a promising combination enhancing wheat (Triticum aestivum L.) growth under chromium stress - Fazal Jalal; Awais Ahmad; Aqib Iqbal; Zafar Hayat Khan; Shah Fahad; Nazia Tahir; Fazal Said; Muhammad Imtiaz; Muhammad Ali Khan; Sayed Hussain; Attaur Rahman; Wasim Khan; et al. (Rhizosphere, 2025)

Experimental design and evaluation of a thermoelectric cold storage system - Faiq Said; Muhammad Aaqib Ishaq; Muhammad Arsalan Khan; Hafiz Basit Ali (Next Research, 2025)

MFCC–ANN model for leak size estimation in pipeline systems - Mohd Fairusham Ghazali; Nor Azinee Said; Muhammad Hanafi Yusop; Erdiwansyah; Muhammad Aminuddin Pi Remli; Rizalman Mamat (Next Research, 2025)

Carbon Nanotubes Improve Quantitative and Qualitative Attributes of Potato (Solanum tuberosum L) Genotypes - Muhammad Ismail; Muhammad Imtiaz; Raham Sher Khan; Fazal Jalal; Fazal Said; Muhammad Ali Khan; Syed Hussain; Badshah Islam; Salman Khan; Sabir Khan; Atta Ullah; Maqsood Khan; et al. (Journal of Soil Science and Plant Nutrition, 2025)

Heavy metals contamination of roadside dust, risk assessment, and their spatial distribution along the M-1 motorway - Sehrish Amin; Wajid Ali; Said Muhammad; Saeeda Yousaf; Ashfaq Ahmad; Umar Farooq (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Water quality, risk assessment indices, and source apportionment across spatial patterns - Said Muhammad; Nizam Ullah; Wajid Ali; Sehrish Amin; Cem Tokatli; Imran Ud Din; Zafar Iqbal; Umar Farooq (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Digital pathways to sustainability: The role of Europe-Central Asia region's digitalization, trade, and geography maximizing sustainable development in China - Umer Shahzad; Said Muhammad (Journal of Environmental Management, 2025)

Multi-objective fuzzy fractional-order BELBIC for semi-active seismic control in non-linear building structures - Muhammad Usman Saeed; Peizhen Li; Said Elias (Engineering Structures, 2025)

Resource recovery from potash brine effluent: integrated chemical precipitation and evaporative crystallization for zero liquid discharge and sustainable brine management - Youssef Amadghous; Yassine Ait-khouia; Abdelmaula Aboulaich; Abdelhak Zagriri; Muhammad Ouabid; Otmane Raji; Said Mansouri; Abdellatif Elghali; Yassine Taha; Mostafa Benzaazoua (Chemosphere, 2025)

Enzymatic responses of fish (Ctenopharyngodon idella) exposed to lethal concentrations of selected trace metals - Nazish Shah; Muhammad Khisroon; Said Sajjad Ali Shah; Abdur Rahim (Environmental Geochemistry and Health, 2025)

Enhanced ammonia nitrogen filtration using NaOH-activated Manihot utilissima peel carbon: Application in recirculating aquaculture systems for Nile tilapia - Said Ali Akbar; Muhammad Hasan; Zulkarnain Jalil; Ilham Zulfahmi; Muhammad Iqhrammullah; Nila Safina (Chemosphere, 2025)

Spatial distribution, potential health risks, and sources of groundwater contamination in the semi-arid region - Owais Rabbani; Wajid Ali; Ghazanfar A. Khattak; Said Muhammad; Muhammad Nafees; Shahid Iqbal; Imran Ud Din; Ashfaq Ahmad; Umar Farooq (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Enhanced electrocatalytic OER performance of Ba/CS-CoFe2O4 ternary heterostructure catalyst: Experimental and theoretical insights - Qirat Yameen; Muhammad Ikram; Sawaira Moeen; Muhammad Imran; Anwar Ul-Hamid; Ghafar Ali; Souraya Goumri-Said; Mohammed Benali Kanoun (Chemosphere, 2025)

Toxicological risk assessment and sources of heavy metal(loid)s using compositional data analysis, Astore River Basin, Himalaya - Wajid Ali; Said Muhammad; Cem Tokatli; Ashfaq Ahmad; Zhang Luyuan (Marine Pollution Bulletin, 2025)

Molecular identification, risk factors’ assessment and phylogenetic analysis of Toxoplasma gondii in goats from Malakand Division, Khyber Pakhtunkhwa, Pakistan - Ahmad Irshad; Shumaila Noreen; Uswa Sajid; Muhsin Jamal; Muhammad Anwar Iqbal; Ubaid Ullah; Talat Sabtain; Shakir Ullah; Eliana Ibañez-Arancibia; Patricio R. De Los Ríos-Escalante; Hanène Belkahia; Mourad Ben Said; et al. (Veterinary Research Communications, 2025)

How Does Corporate Governance Deviance Impact Sustainability in Family Firms? A Stakeholder Perspective - Irfan Saleem; Muhammad Naeem; Muhammad Haseeb; Hao Ji; Said Al Fazari (Circular Economy and Sustainability, 2025)

Magnetic exploration for geothermal power: a case study of Tattapani thermal spring - Mehboob Ur Rashid; Waqas Ahmed; Said Muhammad; Mohammad Arsalan Khan; Adham E. Ragab; Mohammad Mursaleen; Manzoore Elahi M. Soudagar (Acta Geophysica, 2025)

Retraction notice to “Multi-attribute optimization of sustainable aviation fuel production-process from microalgae source” [Fuel 324(Part C) (2022) 124759] - Zafar Said; Tuan Hai Nguyen; Prabhakar Sharma; Changhe Li; Hafiz Muhammad Ali; Van Nhanh Nguyen; Van Viet Pham; Shams Forruque Ahmed; Dong Nguyen Van; Thanh Hai Truong (Fuel, 2025)

Spatial distribution of hazard index via heavy metals consumption in water from the himalayan lacustrine ecosystems - Said Muhammad; Tauseef Ahmed; Sehrish Amin; Cem Tokatli; Fikret Ustaoğlu; Ashfaq Ahmad; Wajid Ali; Umar Farooq (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Spatiotemporal variation of organic contaminants and their ecotoxicological risk in the Uluabat lake basin, Türkiye: A Ramsar living wetland - Cem Tokatlı; Alper Uğurluoğlu; Said Muhammad (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Tuning electronic properties of NiCo2S4 nanofibers through phosphorous doping for optimized oxygen reduction and evolution reactions in Li-O2 batteries - Sana Shoukat; Yichuan Dou; Mingzhu Gao; Dongning Wan; Muhammad Shoaib; Sikandar Iqbal; Amina Tariq; Irum Rafique; Amir Said; Songze Li; Imran Haider; Jun Wang (Chemical Engineering Journal, 2025)

Eco-toxicological study, characterization, distribution and sourcing of persistent organochlorine pesticides in Shalatin (Halayeb Triangle) sediment samples - Tarek O. Said; Safaa Ragab; Amany El Sikaily; Muhammad Arshad; Mohamed A. Hassaan; Murat Yilmaz; Ahmed El Nemr (Environmental Geochemistry and Health, 2025)

Reclaiming Wolffia arrhiza as fish feed for the phytoremediation of aquaculture effluent - Nor Sakinah Mohd Said; Muhammad Zahin Zakaria; Norsyasmin Izzati Samsuddin; Nur Aina'a Zafirah Barom; Navieen AL. M. Murugiah; Siti Rozaimah Sheikh Abdullah (Journal of Environmental Management, 2025)

Enhancing defense and production efficiency in rainbow trout (Oncorhynchus mykiss) through prophylactic dietary selenium and vitamin E fortification - Said Jasim Shah; Noor Khan; Mahroze Fatima; Sheeza Bano; Ayesha Tanveer; Sadia Nazir; Muhammad Asghar; Ahmed Mustafa; Maryam Tahir; Saba Aftab; Alex Hing Leung Wan; Simon John Davies (Animal Feed Science and Technology, 2025)

Digital and geographical mobility: correlating technological bilateral trade impact on sustainable trade development between China and East Asia - Umer Shahzad; Changhong Miao; Said Muhammad (Environment, Development and Sustainability, 2025)

Sperm acrosome-associated 1 (SPACA1) mRNA and protein molecules deficiency indicate low fertility and semen quality of Bali bulls (Bos sondaicus) - Muhammad Agil; Berlin Pandapotan Pardede; Bambang Purwantara; Raden Iis Arifiantini; Hasbi Hasbi; Herry Sonjaya; Syahruddin Said; Suyadi Suyadi; Wike Andre Septian; Chairdin Dwi Nugraha; Rafika Febriani Putri; Ari Ardianto; et al. (Theriogenology, 2025)

Radon contamination, risk evaluation, and their spatial distribution in groundwater of three selected northern districts - Said Muhammad; Rizwan Ullah; Sehrish Amin; Ashfaq Ahmad (Journal of Geochemical Exploration, 2025)

Recent advances in engineering non-native microorganisms for poly(3-hydroxybutyrate) production - Said Nawab; Muhammad Wajid Ullah; Syed Bilal Shah; Ya-Fei Zhang; Hareef Ahmed Keerio; Yang-Chun Yong (World Journal of Microbiology and Biotechnology, 2025)

First report of Hepatozoon and Lankesterella spp. infections in wild rodents from Pakistan, and their potential impact on blood parameters and oxidative stress markers in vital organs - Maryam Ijaz; Asmat Ullah Khan; Muhammad Ali; Shakir Ullah; Muhammad Naeem; Samir Ibenmoussa; Turki M. Dawoud; Adil Khan; Mourad Ben Said; Furhan Iqbal (Veterinary Research Communications, 2025)

Phytotreatment of tofu effluent using water lettuce (Pistia stratiotes) and potential of biogas production from resultant biomass - Setyo Budi Kurniawan; Muhammad Fauzul Imron; Rikky Ramadhan Mustofa; Dhuroton Najiya; Nor Sakinah Mohd Said; Junaidah Buhari; Hajjar Hartini Wan Jusoh; Azimah Ismail (Journal of Water Process Engineering, 2025)

Spatial distribution of groundwater quality and risk indices evaluation via consumption - Said Muhammad; Rizwan Ullah; Sehrish Amin; Haseeb Haroon; Ashfaq Ahmad (Physics and Chemistry of the Earth, Parts A/B/C, 2024)

Potentially harmful elements contamination, risk assessment, and their bioaccumulation in food crops - Imran Ud Din; Said Muhammad; Cem Tokatli; Inayat ur Rehman; Wajid Ali; Mohammed Rafi Shaik; Mohamed E. Assal; Ayaz Ul Haq; Shaik Althaf Hussain (Physics and Chemistry of the Earth, Parts A/B/C, 2024)

Characterization and health risk assessment of n-alkanes and PAHs in sediments from Shalateen (Halayeb Triangle), Egyptian Red Sea Coast - Tarek O. Said; Safaa Ragab; Amany El Sikaily; Muhammad Arshad; Mohamed A. Hassaan; Murat Yılmaz; Ahmed El Nemr (Environmental Pollution, 2024)

Spatial distribution of heavy metal contamination and risk indices of surface sediments in high-altitude lakes - Said Muhammad; Tauseef Ahmed; Rizwan Ullah; Cem Tokatli; Ashfaq Ahmad (Environmental Monitoring and Assessment, 2024)

Bioactivities of natural product geodin congeners and their preliminary structure activity relationship - Gulab Said; Amjad Ali; Muhammad Umair; Farooq Ahmad; Salma Gul; Muhammad Ateeq (Natural Product Research, 2024)

Assessing climate change vulnerability in coastal communities: a composite vulnerability index approach in Kuala Gula, Malaysia - Fathin Faizah Said; Muhammad Muzammil Kamis; Khairul Nizam Abdul Maulud; Azmafazilah Jauhari; Nafisah Mohammed (Environment, Development and Sustainability, 2024)

Spatial distribution of potentially toxic elements pollution and ecotoxicological risk of sediments in the high-altitude lakes ecosystem - Said Muhammad; Aasim Zeb; Mohammed Rafi Shaik; Mohamed E. Assal (Physics and Chemistry of the Earth, Parts A/B/C, 2024)

Spatiotemporal variations, source identification, and risk assessment of potentially toxic elements in the surface water of Felent Stream impacted by the silver mine - Cem Tokatlı; Fikret Ustaoğlu; Said Muhammad; Bayram Yüksel (Environmental Monitoring and Assessment, 2024)

Correction: Spatial distribution of physicochemical parameters and drinking and irrigation water quality indices in the Jhelum River - Tofeeq Ahmad; Said Muhammad; Muhammad Umar; Muhammad Usman Azhar; Alaa Ahmed; Ashfaq Ahmad; Rizwan Ullah (Environmental Geochemistry and Health, 2024)

Tailoring structural and optical properties of Cu(II)-induced MgAl2O4 nanoparticles and their response to toxic dyes under solar illumination - Muhammad Javed; Naeem Akbar; Ayaz Arif Khan; Asad Masood; Naeem Ahmed; Muhammad Junaid Khan; Nisar Ahmed; Said Nasir Khisro; Muhammed Ali Shaikh Abdul Hameed (Environmental Science and Pollution Research, 2024)

Spatial distribution of physicochemical parameters and drinking and irrigation water quality indices in the Jhelum River - Tofeeq Ahmad; Said Muhammad; Muhammad Umar; Muhammad Usman Azhar; Alaa Ahmed; Ashfaq Ahmad; Rizwan Ullah (Environmental Geochemistry and Health, 2024)

Appraisal of metallic accumulation in the surface sediment of a fish breeding dam in Türkiye: A stochastical approach to ecotoxicological risk assessment - Bayram Yüksel; Fikret Ustaoğlu; Handan Aydın; Cem Tokatlı; Halim Topaldemir; Md Saiful Islam; Said Muhammad (Marine Pollution Bulletin, 2024)

Spatial distribution of drinking, irrigation water quality, and health risk indices of high-altitude lakes - Said Muhammad; Aasim Zeb; Rizwan Ullah; Sehrish Amin; Ashfaq Ahmad; Cem Tokatli (Physics and Chemistry of the Earth, Parts A/B/C, 2024)

In-depth characterization of particulate matter in a highly polluted urban environment at the foothills of Himalaya–Karakorum Region - Bahadar Zeb; Khan Alam; Zhongwei Huang; Fatma Öztürk; Peng Wang; Lyudmila Mihaylova; Muhammad Fahim Khokhar; Said Munir (Environmental Science and Pollution Research, 2024)

Spatiotemporal variations, health risk assessment, and sources of potentially toxic elements in potamic water of the Anday Stream Basin (Türkiye), Black Sea Region - Cem Tokatli; Ekrem Mutlu; Fikret Ustaoğlu; Abu Reza Towfiqul Islam; Said Muhammad (Environmental Monitoring and Assessment, 2024)

Evaluation of irrigation, drinking, and risk indices for water quality parameters of alpine lakes - Rizwan Ullah; Said Muhammad; Wajid Ali; Sehrish Amin; Sardar Khan; Atta Rasool; Abd El-Latif Hesham; Muhammad Umar; Shaukat Ali; Shahid Iqbal; Ashfaq Ahmad (Environmental Geochemistry and Health, 2024)

Spatial distribution and potential health risk assessment for fluoride and nitrate via water consumption in Pakistan - Imran Ud Din; Wajid Ali; Said Muhammad; Mohammed Rafi Shaik; Baji Shaik; Inayat ur Rehman; Cem Tokatli (Journal of Geochemical Exploration, 2024)

Reservoir porosity assessment and anomaly identification from seismic attributes using Gaussian process machine learning - Maulana Hutama Rahma Putra; Maman Hermana; Ida Bagus Suananda Yogi; Touhid Mohammad Hossain; Muhammad Faris Abdurrachman; Said Jadid A. Kadir (Earth Science Informatics, 2024)
Porosity, as one of the reservoir properties, is an important parameter to numerous studies, i.e., the reservoir’s oil/gas volume estimation or even the storage capacity measurement in the Carbon Capture Storage (CCS) project. However, an approach to estimate porosity using elastic property from the inversion propagates its error, affecting the result’s accuracy. On the other hand, direct estimation from seismic data is another approach to estimating porosity, but it poses a high non-linear problem. Thus, we propose the non-parametric machine learning approach, Gaussian Process (GP), which draws distribution over the function to solve the high non-linear problem between seismic data with porosity and quantify the prediction uncertainty simultaneously. With the help of Random Forest (RF) as the feature selection method, the GP predictions show excellent results in the blind test, a well that is completely removed from the training data, and comparison with other machine learning models. The uncertainty, standard deviation from GP prediction, can act as a quantitative evaluation of the prediction result. Moreover, we generate a new attribute based on the quartile of the standard deviation to delineate the anomaly zones. High anomaly zones are highlighted and associated with high porosity from GP and low inverted P-impedance from inversion results. Thus, applying the GP using seismic data shows its potential to characterize the reservoir property spatially, and the uncertainty offers insights into quantitative and qualitative evaluation for hydrocarbon exploration and development.

Governance, fiscal expenditure, and economic growth in OIC countries: Role of natural resources and information communication technology - Naila Erum; Kazi Sohag; Jamaliah Said; Kazi Musa; Muhammad Mansoor Asghar (Resources Policy, 2024)

How do air quality, economic growth and energy use affect life expectancy in the Republic of Kazakhstan? - Orazaliyev Kanat; Zhijun Yan; Naila Erum; Muhammad Mansoor Asghar; Syed Anees Haider Zaidi; Jamaliah Said (Air Quality, Atmosphere & Health, 2024)

Bovine nucleoprotein transitions genes and protein abundance as valuable markers of sperm motility and the correlation with fertility - Berlin Pandapotan Pardede; Ni Wayan Kurniani Karja; Syahruddin Said; Ekayanti Mulyawati Kaiin; Muhammad Agil; Cece Sumantri; Bambang Purwantara; Iman Supriatna (Theriogenology, 2024)

Integration of chitosan coating and short-term hypobaric treatment extends postharvest life and upregulates defense-related enzymes in apple fruit - Syed Umair Shah; Majid S. Hashmi; Muhammad Rafiullah Khan; Ayaz Ahmad; Aysha Riaz; Yosef Al Shoffe; Said Wahab; Muhammad Ayub; Antonio Ippolito (European Journal of Plant Pathology, 2024)

Temporal variation of water quality parameters in the lacustrine of the Thrace Region, Northwest Türkiye - Cem Tokatlı; Abu Reza Md. Towfiqul Islam; Said Muhammad (Environmental Science and Pollution Research, 2024)

Heavy metal(loid)s contamination and ecotoxicological hazards in coal, dust, and soil adjacent to coal mining operations, Northwest Pakistan - Imran Ud Din; Said Muhammad; Shah Faisal; Inayat ur Rehman; Wajid Ali (Journal of Geochemical Exploration, 2024)

Compositional data analysis of heavy metal contamination and eco-environmental risks in Himalayan agricultural soils, northern Pakistan - Wajid Ali; Said Muhammad (Journal of Geochemical Exploration, 2023)

Industrial wastewater irrigation increased higher heavy metals uptake and expansins, metacaspases, and cystatin genes expression in Parthenium and maize - Kinza Penzy; Said Muhammad; Muhammad Shahzad; Imran Hussain; Sabaz Ali Khan; Arshad Mehmood Abbasi; Imtiaz Khan; Rafiq Ahmad (Environmental Monitoring and Assessment, 2023)

Annual effective dose estimation of radon in drinking water sources of Nizampur basin, North Western Pakistan - Jehangir Ijaz; Wajid Ali; Said Muhammad; Hayat Ullah; Danish Ather; Imran Ud Din (Isotopes in Environmental and Health Studies, 2023)

Pollution characteristics, sources and health risks assessment of potentially hazardous elements in sediments of ten ponds in the Saros Bay region (Türkiye) - Cem Tokatlı; Memet Varol; Fikret Ustaoğlu; Said Muhammad (Chemosphere, 2023)

DNA base analysis: An effective tool to resolve taxonomic uncertainty and establish phylogenetic relationship in cryptic genotypes of Pyrus (pear), Rosaceae - Muhammad Saeed Akhtar; Shahid Ullah Khan; Ebraheem Abdu Musad Saleh; Said Muhammad; Mohammad Islam; Umber Zaman; Khalil ur Rehman; Gul Nawab; Muhammad Naveed Akhtar; Nabil A. Alhakamy; M.K. Rasha Ibrahim; Ehab A. Abdelrahman (South African Journal of Botany, 2023)

Comprehensive evaluation of hydro-chemical processes, suitability, health risks, and sources of groundwater contamination using compositional data analysis, Nizampur basin, Pakistan - Assad Ullah; Wajid Ali; Said Muhammad; Jehangir Ijaz; Faseeha Amir; Shahid Iqbal (Groundwater for Sustainable Development, 2023)

Spatial distribution of potentially toxic elements contaminations and risk indices of water and sediments in the Darband and Samana streams, Pakistan - Imran Ud Din; Said Muhammad; Inayat ur Rehman; Cem Tokatli (Environmental Monitoring and Assessment, 2023)

Stromeyerite, mckinstryite and jalpaite from the Tagmout Ag–Cu deposit, Eastern Saghro, Morocco: Mineralogical insights and possible origin - Azizi Moussaid; Mohamed Aissa; Panagiotis Voudouris; Hafid Mezougane; Mohamed Benbrahim; Said Ilmen; Mohamed El Azmi; Muhammad Souiri; Ilyasse Loudaoued; Ilya Prokopyev (Journal of African Earth Sciences, 2023)

Spatial and temporal distribution of heavy metals pollution and risk indices in surface sediments of Gomal Zam Dam Basin, Pakistan - Said Muhammad; Insha Ullah (Environmental Monitoring and Assessment, 2023)

Ecotoxicological evaluation of organic contamination in the world's two significant gateways to the Black Sea using GIS techniques: Turkish Straits - Cem Tokatlı; Alper Uğurluoğlu; Said Muhammad (Marine Pollution Bulletin, 2023)

Strategic resources alignment for sustainability: The impact of innovation capability and intellectual capital on SME's performance. Moderating role of external environment - Muhammad Zulqarnain Arshad; Darwina Arshad; Hendrik Lamsali; Ahmad Said Ibrahim Alshuaibi; Mohammad Said Ibrahim Alshuaibi; Gadah Albashar; Awais Shakoor; Lai Fatt Chuah (Journal of Cleaner Production, 2023)

Chlorinated pesticides and PCB residues in the Egyptian Western Desert oases sediments - Tarek O. Said; Safaa Ragab; Amany El Sikaily; Mohamed A. Hassaan; Muhammad Arshad; Ahmed El Nemr (Marine Pollution Bulletin, 2023)

Effects of injection parameters and intake air temperature on acetone-butanol-ethanol (ABE) blend HCCI-DI engine - Muhammad Faizullizam Roslan; Ibham Veza; Mohd Farid Muhamad Said (Fuel, 2023)

Origin of Cretaceous alkaline annular structures in the peri-cratonic terranes of the Reguibat Rise in Morocco: New constraints from carbonatite–silicate pairs and subsolidus processes - Cheikh-Elwali Malainine; Muhammad Ouabid; Otmane Raji; Jean-Louis Bodinier; Fleurice Parat; Hicham El Messbahi; Jean-Marie Dautria; Es-Said Jourani; Oussama Khadiri Yazami; Carlos J. Garrido (Chemical Geology, 2023)

Spatial distribution of radon contamination in hot springs water and its cancer and non-cancer risks in the Hunza-Nagar valley, Pakistan - Said Muhammad; Anwarul Haq (Environmental Geochemistry and Health, 2023)

Geospatial soil loss risk assessment using RUSLE model: a study of Panjkora River Basin, Khyber Pakhtunkhwa, Pakistan - Muhammad Jamal Nasir; Said Alam; Waqas Ahmad; Sayed M. Bateni; Javed Iqbal; Mansour Almazroui; Burhan Ahmad (Arabian Journal of Geosciences, 2023)

Arsenic Speciation in Rice, Mechanisms and Associated Health Risk Through Rice Consumption in Various Districts of Khyber Pakhtunkhwa, Pakistan - Tasneem Sarwar; Sardar Khan; Javed Nawab; Said Muhammad; Shehla Amin; Janas Khan; Adnan Sarwar; Iqbal Haider; Qing Huang (Exposure and Health, 2023)

Spatial distribution, eco-environmental risks, and source characterization of heavy metals using compositional data analysis in riverine sediments of a Himalayan river, Northern Pakistan - Wajid Ali; Said Muhammad (Journal of Soils and Sediments, 2023)

Heavy metal(loid)s contaminations in soils of Pakistan: a review for the evaluation of human and ecological risks assessment and spatial distribution - Imran Ud Din; Said Muhammad; Inayat ur Rehman (Environmental Geochemistry and Health, 2023)

Cellulose/inorganic nanoparticles-based nano-biocomposite for abatement of water and wastewater pollutants - Zhen Zhang; Abdulrazaq Ibrahim Said Ahmed; Muhammad Zeeshan Malik; Nisar Ali; Adnan khan; Farman Ali; Mohamed Osman Hassan; Badr A. Mohamed; Jakub Zdarta; Muhammad Bilal (Chemosphere, 2023)

Heavy metal(loid)s contamination and potential risk assessment via groundwater consumption in the district of Hangu, Pakistan - Imran Ud Din; Said Muhammad; Shah Faisal; Inayat ur Rehman; Wajid Ali (Environmental Science and Pollution Research, 2022)

Evaluation of heavy metals in water and sediments, pollution, and risk indices of Naltar Lakes, Pakistan - Said Muhammad (Environmental Science and Pollution Research, 2022)

Potentially Harmful Elements Accumulation and Health Risk Assessment of Edible Fish Tissues Caught from the Phander Valley, Northern Pakistan - Said Muhammad; Wajid Ali; Inayat ur Rehman (Biological Trace Element Research, 2022)

Spatial distribution of drinking and irrigation water quality indices of Ghizer River Basin, northern Pakistan - Ayaz Ul Haq; Said Muhammad (Environmental Science and Pollution Research, 2022)

Assessment of municipal solid waste landfilling practices on the groundwater quality and associated health risks: a case study of Mardan-Pakistan - Muhammad Israr; Shahla Nazneen; Ali Raza; Neelum Ali; Said Akbar Khan; Hizbullah Khan; Sardar Khan; Jawad Ali (Arabian Journal of Geosciences, 2022)

A Comparative Analysis of Adopters and Non‐adopters of Drip Irrigation under Plastic Tunnels for Cucumber ( Cucumis sativus L.) Production in Balochistan, Pakistan - Said Qasim; Muhammad Qasim; Anees Hassan; Ghulam Murtaza; Amir Nawaz Khan (Irrigation and Drainage, 2022)
This research tries to compare the water use efficiency, electricity efficiency and economic efficiency of adopters and non‐adopters of drip irrigation under plastic tunnels (DIUPT). Data regarding the socio‐economic conditions of farmers and their views on the advantages and disadvantages of the DIUPT were collected through a questionnaire survey of 200 farmers. For expenses, income, electricity efficiency and water use efficiency, we collected data only from the sample farmers, i.e. one adopter and one non‐adopter. Results also revealed that the total horsepower (HP) hours of water per acre used for drip‐irrigated cucumber under plastic tunnels was 240 compared to 576 HP hours for the flood method of irrigation, thereby saving 58% (336 HP hours) of energy. In other words, with the same amount of water used for irrigating 1 acre of cucumber under flood irrigation, 2.4 acres of cucumber could be irrigated using drip irrigation. Realizing about 51% higher yields under drip irrigation, adopters enjoy 40% higher returns than non‐adopter farmers. The study recommends dissemination of information to farmers about DIUPT through training and seminars. Adoption of these technologies would lead to efficient and sustainable use of already depleting water resources in the drought‐prone province of Balochistan.

First report on molecular surveillance based on duplex detection of Anaplasma marginale and Theileria annulata in dairy cattle from Punjab, Pakistan - Farhan Ahmad Atif; Rao Zahid Abbas; Saba Mehnaz; Muhmmad Fiaz Qamar; Kashif Hussain; Muhammad Usman Nazir; Muhammad Arfan Zaman; Aman Ullah Khan; Mourad Ben Said (Tropical Animal Health and Production, 2022)

Spatial and seasonal variation of water quality indices in Gomal Zam Dam and its tributaries of south Waziristan District, Pakistan - Said Muhammad; Insha Ullah (Environmental Science and Pollution Research, 2022)

Feeding niche overlap between native and alien fishes in Swat River, Khyber Pakhtunkhwa, Pakistan - Amir Said; Muhammad Imran; Muhammad Tahir Waseem; Abdul Majid Khan; Noman Khalique; Ghulam Sarwar; Rana Manzoor Ahmad (Environmental Biology of Fishes, 2022)

Heavy metal bioavailability in the earthworm-assisted soils of different land types of Pakistan - Fouzia Bakht; Sardar Khan; Said Muhammad; Muhammad Amjad Khan (Arabian Journal of Geosciences, 2022)

Wheat Genotypes with Higher Intercellular CO2 Concentration, Rate of Photosynthesis, and Antioxidant Potential Can Better Tolerate Drought Stress - Aman Ullah; Rashid Said Al-Rajhi; Abdullah M. Al-Sadi; Muhammad Farooq (Journal of Soil Science and Plant Nutrition, 2021)

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Metal accumulation potential, human health risks, and yield attributes of hundred bread wheat genotypes on irrigation with municipal and remediated wastewater - Said Akbar; Zeshan Ali; Sadam Hussain; Ashiq Mohammad; Yousaf Riaz; Adnan Shakeel; Ijaz Ahmad; Maria Mussarat; Riffat Naseem Malik; Kiran Yasmin Khan; Muhammad Sohail; Umar Masood Quraishi (Environmental Science and Pollution Research, 2021)

Metals Distribution, Histopathological Alterations, and Health Risk Assessment in Different Tissues of Fish (Ctenopharyngodon idella) - Nazish Shah; Muhammad Khisroon; Said Sajjad Ali Shah (Biological Trace Element Research, 2021)

Levels of polychlorinated dibenzo-p-dioxins and dibenzofurans (PCDD/Fs) in municipal waste dumping site, incinerator and brick kiln residues: evaluation for potential risk assessment - Nida Gul; Bushra Khan; Hizbullah Khan; Said Muhammad; Iqbal Ahmad; Nayab Gul (Arabian Journal of Geosciences, 2021)

Essential oil composition of Alseodaphne perakensis (Gamble) Kosterm from Malaysia - Muhammad Zul Afiq Anuar; Wan Mohd Nuzul Hakimi Wan Salleh; Shamsul Khamis; Mohd Azlan Nafiah; Zahid Mat Said (Natural Product Research, 2021)

Lead contamination in shooting range soils and its phytoremediation in Pakistan: a greenhouse experiment - Amir Zeb Khan; Sardar Khan; Said Muhammad; Shams Ali Baig; Abdullah Khan; Muhammad Jamal Nasir; Madiha Azhar; Alia Naz (Arabian Journal of Geosciences, 2021)

Potentially toxic elements’ occurrence and risk assessment through water and soil of Chitral urban environment, Pakistan: a case study - Inayat ur Rehman; Muhammad Ishaq; Liaqat Ali; Said Muhammad; Imran Ud Din; Muhammad Yaseen; Hameed Ullah (Environmental Geochemistry and Health, 2020)

Evaluation of the Swat River, Northern Pakistan, water quality using multivariate statistical techniques and water quality index (WQI) model - Shah Jehan; Ihsan Ullah; Sardar Khan; Said Muhammad; Seema Anjum Khattak; Tariq Khan (Environmental Science and Pollution Research, 2020)
This study evaluates the characteristics of water along the Swat River, Northern Pakistan. For this purpose, water samples ( n = 30) were collected and analyzed for physicochemical parameters including heavy metals (HM). The mean concentrations of physicochemical parameters and HM were within the drinking water guideline values set by the World Health Organization (WHO 2011) except 34%, 60%, and 56% of copper (Cu), nickel (Ni), and lead (Pb), respectively. Pollution sources were identified by various multivariate statistical techniques including correlation analysis (CA) and principal component analysis (PCA) indicating different origins both naturally and anthropogenically. Results of the water quality index (WQI) ranged from 13.58 to 209 with an average value of 77 suggesting poor water quality for drinking and domestic purposes. The poor water quality was mainly related to high sodium (alkalinity) and salinity hazards showing > 27% and 20% water samples have poor alkalinity and salinity hazards, respectively. Hazard quotient (HQ) and hazard index (HI) were used to determine the health risk of HM in the study area. For water-related health risk, HQ ingestion , HQ dermal , and HI values were > 1, indicating noncarcinogenic health risk (NCR) posed by these HM to the exposed population.

Risk assessment of hazardous elements in wastewater irrigated soil and cultivated vegetables in Pakistan - Alia Naz; Sardar Khan; Said Muhammad; Rafiq Ahmad; Salma Khalid; Abdullah Khan; Rashid Nazir; Sadia Alam; Zia ur Rahman (Arabian Journal of Geosciences, 2020)

Genome-wide analysis of glutathione S-transferase gene family in G. max - Muhammad Zulfiqar Ahmad; Jamal Abdul Nasir; Shakeel Ahmed; Bushra Ahmad; Aiman Sana; Said Salman; Zamarud Shah; CunYi Yang (Biologia, 2020)

An indicator based approach for assessing household’s perceptions of landslide risk in Murree hills of Pakistan - Said Qasim; Muhammad Qasim (Natural Hazards, 2020)

Assessment of copper, chromium, and lead toxicity in fish (Ctenopharyngodon idella Valenciennes, 1844) through hematological biomarkers - Nazish Shah; Muhammad Khisroon; Said Sajjad Ali Shah (Environmental Science and Pollution Research, 2020)

Radon concentration in drinking water and soil after the September 24, 2019, Mw 5.8 earthquake, Mirpur, Azad Jammu, and Kashmir: an evaluation for potential risk - Said Muhammad; Rizwan Ullah; Syed Ali Turab; Muhammad Younis Khan; Nimat Ullah Khattak; Muhammad Asif Khan (Environmental Science and Pollution Research, 2020)

Date palm rachis as a raw material for wood composite industry: anatomical characteristics - Pervaiz Rasheed Khan; Said Saad Hegazy; Muhammad Iqbal (Brazilian Journal of Botany, 2020)

Light intensity effects on the growth and biomass production of submerged macrophytes in different water strata - Shuquan Jin; Muhammad Ibrahim; Said Muhammad; Sardar Khan; Gang Li (Arabian Journal of Geosciences, 2020)

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Use of subsurface temperature as a groundwater flow tracer in the environs of Ismailia Canal, Eastern Nile Delta, Egypt - Zenhom El-Said Salem; Mohamed Sobhy Fathy; Abdel-Fattah Ibrahim Helal; Sofia Yahia Afifi; Abdullah Muhammad Attiah (Arabian Journal of Geosciences, 2020)

Ingestion of Arsenic-Contaminated Drinking Water Leads to Health Risk and Traces in Human Biomarkers (Hair, Nails, Blood, and Urine), Pakistan - Ubaid ur Rehman; Sardar Khan; Said Muhammad (Exposure and Health, 2020)

Synthesis of Ligand Functionalized ErbB-3 Targeted Novel DNA Nano-Threads Loaded with the Low Dose of Doxorubicin for Efficient In Vitro Evaluation of the Resistant Anti-Cancer Activity - Mirza Muhammad Faran Ashraf Baig; Wing-Fu Lai; Anam Ahsan; Mehreen Jabeen; Muhammad Asim Farooq; Reyaj Mikrani; Muhammad Abbas; Muhammad Naveed; Said Abasse Kassim; Faisal Raza; Afzal Ahmed Dar; Muhammad Tayyab Ansari (Pharmaceutical Research, 2020)

Photocatalytic Degradation of Congo Red Dye from Aqueous Environment Using Cobalt Ferrite Nanostructures: Development, Characterization, and Photocatalytic Performance - Nisar Ali; Amir Said; Farman Ali; Fazal Raziq; Zarshad Ali; Muhammad Bilal; Laurence Reinert; Tasleem Begum; Hafiz M. N. Iqbal (Water, Air, & Soil Pollution, 2020)

Isolation and functional characterization of an Ethylene Response Factor (RhERF092) from rose (Rosa hybrida) - Muhammad Ali Khan; Muhammad Imtiaz; Adil Hussain; Fazal Jalal; Sikandar Hayat; Sayed Hussain; Fazal Said; Mehboob Alam; Rabia Amir (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Human health risks by potentially toxic metals in drinking water along the Hattar Industrial Estate, Pakistan - Shah Jehan; Seema Anjum Khattak; Said Muhammad; Liaqat Ali; Abdur Rashid; Mian Luqman Hussain (Environmental Science and Pollution Research, 2020)

Mercury Contamination in Water and Sediments and the Associated Health Risk: A Case Study of Artisanal Gold-mining - Arjumand Riaz; Sardar Khan; Said Muhammad; Mohammad Tahir Shah (Mine Water and the Environment, 2019)

Acaricidal efficacy of Calotropis procera (Asclepiadaceae) and Taraxacum officinale (Asteraceae) against Rhipicephalus microplus from Mardan, Pakistan - Adil Khan; Nasreen Nasreen; Sadaf Niaz; Sultan Ayaz; Huma Naeem; Ijaz Muhammad; Fazal Said; Robert D. Mitchell; Adalberto A. Pérez de León; Snehil Gupta; Sachin Kumar (Experimental and Applied Acarology, 2019)

Human Health Risk Assessment Through Consumption of Organophosphate Pesticide-Contaminated Water of Peshawar Basin, Pakistan - Neelum Ali; Kalsoom; Sardar Khan; Ihsanullah; Inayat ur Rahman; Said Muhammad (Exposure and Health, 2018)

Effect of body weight on the chemical composition and collagen content of snakehead fish Channa striata skin - Rosmawati; Effendi Abustam; Abu Bakar Tawali; Muhammad Irfan Said; Dwi Kesuma Sari (Fisheries Science, 2018)

Associations of potentially toxic elements (PTEs) in drinking water and human biomarkers: a case study from five districts of Pakistan - Ubaid ur Rehman; Sardar Khan; Said Muhammad (Environmental Science and Pollution Research, 2018)

Potentially toxic elements in soil of the Khyber Pakhtunkhwa province and Tribal areas, Pakistan: evaluation for human and ecological risk assessment - Umar Saddique; Said Muhammad; Mohsin Tariq; Hua Zhang; Mohammad Arif; Ishtiaq A. K. Jadoon; Nimat Ullah Khattak (Environmental Geochemistry and Health, 2018)

Vehicular emissions on main roads in Makkah, Saudi Arabia—a dispersion modelling study - Said Munir; Turki Muhammad Habeebullah (Arabian Journal of Geosciences, 2018)

Potential harmful elements in coal dust and human health risk assessment near the mining areas in Cherat, Pakistan - Muhammad Ishtiaq; Noor Jehan; Said Akbar Khan; Said Muhammad; Umar Saddique; Bushra Iftikhar; Zahidullah (Environmental Science and Pollution Research, 2018)

A novel Salvialactomine from the callus culture of Salvia santolinifolia Boiss - Tour Jan; Raiha Qadri; Beena Naqvi; Achyut Adhikari; Said Nadeem; Akhtar Muhammad (Natural Product Research, 2018)

Mercury contamination in selected foodstuffs and potential health risk assessment along the artisanal gold mining, Gilgit-Baltistan, Pakistan - Arjumand Riaz; Sardar Khan; Said Muhammad; Caihong Liu; Mohammad Tahir Shah; Mohsin Tariq (Environmental Geochemistry and Health, 2018)

Photocatalytic Degradation of Pentachlorophenol Using ZnO Nanoparticles: Study of Intermediates and Toxicity - Muneer M. Ba-Abbad; Mohd S. Takriff; Muhammad Said; Abdelbaki Benamor; Mustafa S. Nasser; Abdul Wahab Mohammad (International Journal of Environmental Research, 2017)

Synthesis, characterization and theoretical calculations of (1,2-diaminocyclohexane)(1,3-diaminopropane)gold(III) chloride complexes: in vitro cytotoxic evaluations against human cancer cell lines - Said S. Al-Jaroudi; Muhammad Altaf; Abdulaziz A. Al-Saadi; Abdel-Nasser Kawde; Saleh Altuwaijri; Saeed Ahmad; Anvarhusein A. Isab (BioMetals, 2015)

Genetic analysis suggests a shared origin of Punica granatum cultivars in Oman with cultivars from the center of origin, Iran - Abdullah M. Al-Sadi; Ahmed R. AL-Fahdi; Rashid A. Al-Yahyai; Aisha G. Al-Ghaithi; Fahad A. Al-Said; Muhammad J. Soleiman (Genetic Resources and Crop Evolution, 2015)

Anthocyanin production in the hyperaccumulator plant Noccaea caerulescens in response to herbivory and zinc stress - Saeed Ahmad Asad; Said Muhammad; Muhammad Farooq; Aftab Afzal; Martin Broadley; Scott Young; Helen West (Acta Physiologiae Plantarum, 2015)

Synthesis, spectroscopic characterization, electrochemical behavior and computational analysis of mixed diamine ligand gold(III) complexes: antiproliferative and in vitro cytotoxic evaluations against human cancer cell lines - Said S. Al-Jaroudi; M. Monim-ul-Mehboob; Muhammad Altaf; Abdulaziz A. Al-Saadi; Mohammed I. M. Wazeer; Saleh Altuwaijri; Anvarhusein A. Isab (BioMetals, 2014)